Comparative Industrial Analysis of Selected Countries with Special Reference to Pakistan: Product Space Perspective - Kamila Hakeem; Amberina Bibi; Nahida Noor; Dr. Syed Fahad Ali Shah; Sajid Ur Rehman (Indus Journal of Social Sciences, 2025)
This study aims to focus on discovering the role of the sophistication in export diversification. The relatedness and connectedness of the products shown in the product space model (PSM) allows countries to accomplish future industrialization in a systematic manner that lead to sustainable economic growth. The acquisition of modern trade policies helps to flourish the unexploited exports. To analyze the impact of export diversification on economic growth, we have taken the cross sectional export data of 150 countries for the year of (2021) and the current study is based on secondary data. Firstly, we find the level of sophistication of a product and then find the overall sophistication of a country for future industrialization. Moreover, the revealed comparative advantage (RCA) index has been used to evaluate the comparative advantage of the selected four South Asian countries namely; Pakistan, India, Bangladesh and Afghanistan and it was found that India has relatively high number of RCA products in its export basket, and thus closer to fully exploit the remaining unexploited, non-RCA products for export diversification, while Pakistan and Bangladesh have moderate level of opportunities considering their position in product space. Afghanistan’s exports are located mostly in the peripheral area of product space, where moving to non-RCA products are relatively more challenging.